A Co / ZnO@PPy composite material and its preparation and application
By preparing Co/ZnO@PPy composite materials, hydrothermal synthesis and in-situ gas-phase polymerization technology are used to form a honeycomb structure, which solves the problem of insufficient performance of existing microwave absorbing materials and achieves the effect of high absorption strength and wide-band response .
Patent Information
- Application Number
- CN202210500474.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-05-09
AI Technical Summary
Existing microwave absorbing materials are difficult to meet the requirements of light weight, harsh environment and strong broadband absorption at the same time, and the single material lacks wave absorption performance, making it difficult to meet the needs of stealth technology.
Co/ZnO@PPy composite material was used to prepare Co/ZnO micron solid columns by hydrothermal synthesis, and polypyrroles (PPy) were coated on its surface through in-situ gas-phase polymerization to form a honeycomb structure, thereby enhancing the material electromagnetic wave absorption performance.
The high absorption strength and wide-band response of micron-scale solid columnar Co/ZnO@PPy composite material are achieved, which enhances the attenuation ability of electromagnetic waves and meets the "thin, light, wide and strong" requirements of stealth technology.
Smart Images

Figure CN115003143B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional material preparation, and relates to a Co / ZnO@PPy composite material and a preparation and application thereof. Background Art
[0002] In recent years, with the rapid development of electronic technology, wireless communication and high-end precision equipment, people have suffered from ubiquitous electromagnetic interference and electromagnetic pollution while enjoying the convenience brought by high technology. These pollutions have brought great inconvenience and harm to people's daily lives and have become the fourth largest pollution after noise pollution, air pollution and water pollution. Therefore, in order to reduce and avoid electromagnetic interference and electromagnetic pollution, microwave absorbing materials have received extensive attention and research. Magnetic materials, graphitized carbon, semiconductors, polymer materials, etc. have been widely studied and applied in the field of microwave absorption by virtue of their own electromagnetic properties. Unfortunately, however, it is difficult for these single materials to simultaneously meet the special requirements of modern microwave absorbers for microwave absorption and impedance matching, such as light weight, harsh environment and strong broadband absorption. Therefore, it is urgent to study the composite method of combining different microwave absorbing materials with complementary properties.
[0003] As an important polarized semiconductor material, ZnO has excellent mechanical, piezoelectric and dielectric properties and has attracted wide attention in many fields. Similarly, ZnO-based materials have also attracted extensive research in the field of microwave absorption. Studies have shown that ZnO-based composites also exhibit excellent dielectric properties at high temperatures [MMLu, WQCao, HLShi, XYFang, J.Yang, ZLHou, HBJin, WZWang, J.Yuan, MSCao, J.Mater.Chem.A 2014, 2, 10540.], and ZnO with different morphologies has enhanced conductivity and polarization [MKHan, XWYin, L.Kong, M.Li, WYDuan, LTZhang, LFCheng, J.Mater.Chem.A 2014, 2, 16403.]. Pure ZnO has high dielectric loss as an absorbing material, but its electrical conductivity is between that of a conductor and an insulator. Its electromagnetic wave absorption performance is only manifested in the high-frequency band. It has defects such as a single absorbing mechanism, weak absorbing ability, and a narrow absorbing frequency band. It is difficult to simultaneously meet the requirements of "thin, light, wide, and strong" put forward by the increasingly developed stealth technology. Summary of the invention
[0004] The purpose of the present invention is to provide a Co / ZnO@PPy composite material and its preparation and application.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the technical solutions of the present invention provides a method for preparing a Co / ZnO@PPy composite material, comprising the following steps:
[0007] (1) adding cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea into deionized water, stirring and dissolving to obtain a clear and transparent mixed solution;
[0008] (2) transferring the mixed solution into a reaction vessel for hydrothermal reaction, washing and drying the obtained reaction product to obtain a precursor powder;
[0009] (3) placing the precursor powder in a hydrogen and argon atmosphere for high-temperature reduction, and then cooling it to room temperature to obtain the intermediate product Co / ZnO;
[0010] (4) Disperse the intermediate product Co / ZnO evenly in FeCl 3 The solvent was evaporated in an ethanol solution, and the obtained powder was ground and placed in the same closed container with the pyrrole monomer without direct contact with each other, and heated to carry out an in-situ gas phase polymerization reaction. The obtained reaction product was washed and freeze-dried to obtain the target product Co / ZnO@PPy.
[0011] Furthermore, in step (1), the molar ratio of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea is (2-5): (1-3): (6-10): (8-14).
[0012] Furthermore, in step (1), the amount of deionized water added satisfies: 2+ The concentration is 0.04~0.12mol / L, Zn 2+ The concentration is 0.01~0.07mol / L.
[0013] Furthermore, in step (2), the temperature of the hydrothermal reaction is 80 to 160° C., and the time is 4 to 8 hours.
[0014] Furthermore, in step (2), the washing process is: using deionized water and ethanol to centrifuge and wash at a speed of 8000-10000 rpm for several times.
[0015] Furthermore, in step (3), the volume fraction of hydrogen in the hydrogen-argon atmosphere used is 4 to 6%.
[0016] Furthermore, in step (3), the high temperature reduction process is specifically: calcining at 500-650° C. for 1-3 hours.
[0017] Furthermore, in step (4), FeCl 3 The concentration of ethanol solution is 3-7 mmol / L, Co / ZnO in FeCl 3The concentration in ethanol solution is 0.1-0.2 g / mL.
[0018] Furthermore, in step (4), the temperature of the in-situ gas phase polymerization reaction is 50 to 65° C., and the reaction time is 2 to 24 hours.
[0019] Furthermore, in step (4), the ratio of the added amount of the intermediate product Co / ZnO to the added amount of the pyrrole monomer is 0.2 g:(1-3) mL.
[0020] Furthermore, in step (4), two open vials are placed in the sealed container, one of which is used to place the powder and the other is used to place the pyrrole monomer, so that the two are not in direct contact with each other.
[0021] The second technical solution of the present invention provides a Co / ZnO@PPy composite material, which is prepared by the preparation method as described above. The composite material is a micrometer-scale solid columnar body with a circular cross-section size of 2 to 3 μm and a honeycomb structure on the surface.
[0022] The third technical solution of the present invention provides an application of a Co / ZnO@PPy composite material, which is used as a microwave absorbing material. Specifically, it can be used as an electromagnetic wave absorbing material. In its specific application, the steps are: uniformly mix the prepared Co / ZnO@PPy composite powder with sliced paraffin in a mass ratio of 1:1. Pour the mixture into an aluminum mold and press it into a ring sample with an inner diameter of 3.0 mm, an outer diameter of 7.0 mm, and a thickness of 2.0 mm. Use a vector network analyzer with model N5230C to test the complex relative dielectric constant and magnetic permeability in the range of 2.0-18.0 GHz.
[0023] For a long time, nanomaterials have been limited by size mismatch and have weak interactions with electromagnetic waves. The conversion capacity of electromagnetic wave energy is generally improved by changing the equivalent electromagnetic parameters of the composite material. ZnO semiconductors have shown superiority in microwave absorption applications due to their high dielectric polarization loss. Dielectric polarization is related to the intrinsic and extrinsic parameters of the material, such as electromagnetic properties and geometric morphology. Based on this, a micron-scale solid columnar Co / ZnO electromagnetic composite material was prepared. By adjusting the reaction time of the in-situ gas phase polymerization reaction, the surface microstructure of the micron-scale solid columnar Co / ZnO@PPy composite material will change significantly, and the structure will affect the electromagnetic parameters and impedance matching characteristics of the material, and finally achieve precise control of the composite material's wave absorption performance. Among them, the 3D network structure is conducive to the rapid transmission of conductive electrons, and the large number of interfaces provided by the surface honeycomb structure is conducive to interface polarization, multiple scattering and impedance matching, thereby greatly enhancing the attenuation ability of the Co / ZnO@PPy composite material to electromagnetic waves.
[0024] The present invention adopts a convenient and efficient hydrothermal synthesis method to prepare the precursor hydroxy zinc cobalt fluoride. After high-temperature reduction in a hydrogen and argon atmosphere, the product Co / ZnO micron solid column is obtained, and then polypyrrole (PPy) is coated on the outside of the Co / ZnO micron solid column through a simple in-situ gas phase polymerization reaction, and the surface presents a honeycomb structure, which shows excellent comprehensive performance in the field of microwave absorption.
[0025] Compared with the prior art, the micrometer-scale solid columnar Co / ZnO@PPy composite material of the present invention exhibits the characteristics of high absorption intensity and wide response frequency band, which is due to the 3D interwoven network conductive network formed by its surface porous honeycomb structure, which provides a path for the transmission of electrons and increases the storage capacity of electromagnetic waves; and the large number of interfaces formed by the defect-rich ZnO and polypyrrole are conducive to the dissipation of electromagnetic waves by interface polarization and multiple scattering, and enhance the dielectric loss. The rich pore structure of the surface honeycomb increases multiple scattering and multiple reflection, further optimizing the impedance matching. This micrometer-scale solid columnar Co / ZnO@PPy composite material with good electromagnetic wave absorption performance, strong dielectric loss and easy preparation has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The scanning electron microscope images of the micrometer-scale solid columnar Co / ZnO and Co / ZnO@PPy in Examples 1 to 5, wherein (a) is a scanning electron microscope image of the micrometer-scale solid columnar Co / ZnO in Examples 1 to 5; (b) is a scanning electron microscope image of the micrometer-scale solid columnar Co / ZnO@PPy in Example 2; (c) is a scanning electron microscope image of the micrometer-scale solid columnar Co / ZnO@PPy in Example 3; (d) is a scanning electron microscope image of the micrometer-scale solid columnar Co / ZnO@PPy in Example 1; (e) is a scanning electron microscope image of the micrometer-scale solid columnar Co / ZnO@PPy in Example 4; (f) is a scanning electron microscope image of the micrometer-scale solid columnar Co / ZnO@PPy in Example 5;
[0027] Figure 2 This is the X-ray diffraction spectrum of Example 1-micrometer-scale solid columnar Co / ZnO@PPy.
[0028] Figure 3 This is Example 1 - relative complex permeability and relative complex dielectric constant of micrometer-scale solid columnar Co / ZnO@PPy, including the real and imaginary parts of the complex permeability, and the real and imaginary parts of the complex dielectric constant.
[0029] Figure 4 It is the electromagnetic wave reflection loss value of micrometer-scale solid columnar Co / ZnO and Co / ZnO@PPy at a thickness of 1.7 mm in Examples 1-5.
[0030] Figure 5 The scanning electron microscope (a) and transmission electron microscope (b) images of the product of Comparative Example 1 are shown. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0032] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0033] Embodiment 1:
[0034] Preparation of Co / ZnO@PPy composites:
[0035] First, 4 mmol Co(NO 3 ) 2 6H 2 O, 1mmol Zn(NO 3 ) 2 6H 2 O, 9mmol NH 4 F, 9mmolCO(NH 2 ) 2 , added into 45 mL of deionized water, and completely dissolved under vigorous magnetic stirring to obtain a uniform and transparent mixed solution.
[0036] Next, the solution was transferred to a Teflon-lined stainless steel hydrothermal reactor and heated at 120°C for 8 hours. After cooling to room temperature, it was washed several times by centrifugation with deionized water and ethanol, and then dried under vacuum at 60°C to collect Zn x Co 1-x (OH)F precursor.
[0037] Then, the precursor powder was placed in a porcelain boat and placed in a tube furnace for high-temperature reduction at 600°C for 2 hours in a hydrogen-argon atmosphere (hydrogen gas volume fraction was 5%), with a heating rate of 2°C / min. -1 After cooling naturally to room temperature, micron-sized Co / ZnO powder was obtained. Its morphology is similar to a cylinder, the circular cross-section size is about 2-3μm, and the surface is a longitudinal flaky structure.
[0038] Finally, 0.2 g of Co / ZnO powder was evenly dispersed in 10 mL of 5 mmol / L FeCl 3The ethanol solution was placed in a vacuum drying oven to evaporate the solvent, and the powder was finely ground and placed in an open small glass bottle. 2 mL of pyrrole monomer was then dripped into another open small glass bottle. The two small glass bottles were placed in the same large glass bottle. The large glass bottle was sealed and placed in a vacuum oven for in-situ gas phase polymerization. The reaction temperature was 55 ° C and allowed to stand for 8 hours. The product was washed several times by centrifugation with ethanol and water, and then freeze-dried to obtain the target product Co / ZnO@PPy.
[0039] Embodiment 2:
[0040] Compared with Example 1, most of them are the same, except that in this example: the in-situ gas phase polymerization reaction time is 2 hours.
[0041] Embodiment 3:
[0042] Compared with Example 1, most of them are the same, except that in this example: the in-situ gas phase polymerization reaction time is 4 hours.
[0043] Embodiment 4:
[0044] Compared with Example 1, most of them are the same, except that in this example: the in-situ gas phase polymerization reaction time is 12 hours.
[0045] Embodiment 5:
[0046] Compared with Example 1, most of the above are the same, except that in this example: the in-situ gas phase polymerization reaction time is 24 hours.
[0047] The microscopic morphology of the micrometer-scale solid columnar Co / ZnO and Co / ZnO@PPy in the above embodiment was characterized by scanning electron microscopy (SEM, Hitachi FE-SEM S-4800), and the powder sample was coated on the surface of the conductive glue for testing. The X-ray diffraction spectrum was measured by a BrukerD8 Advance instrument. The complex relative permeability and complex relative permittivity in the range of 2.0-18.0 GHz were tested using a vector network analyzer model N5230C, and the reflection loss values at different thicknesses were obtained by calculation and fitting.
[0048] Figure 1The scanning electron microscope images of the micrometer-scale solid columnar Co / ZnO and Co / ZnO@PPy synthesized in the above-mentioned Examples 1-5 are shown. As shown in the figure, the morphology of Co / ZnO is similar to a cylinder, the circular cross-section size is about 2 to 3 μm, and the surface is a longitudinal flaky structure. After in-situ gas phase polymerization with pyrrole monomer, the product size and morphology did not change significantly, but the polymerization reaction time had a great influence on the surface of the composite product. The morphology of Example 2 is similar to a cylinder, the circular cross-section size is about 2 to 3 μm, and the surface is irregularly convex. The morphology of Examples 1, 3 to 4 is similar to a cylinder, the circular cross-section size is about 2 to 3 μm, and the surface is a honeycomb structure. Compared with Example 2, due to the extended in-situ gas phase polymerization time, the reaction is more complete, but the surface agglomeration is serious if the time is too long. The morphology of Example 5 is similar to a cylinder, the circular cross-section size is about 4 μm, and the surface is solid. Therefore, the in-situ gas phase polymerization reaction time is an important condition for the evolution of the surface morphology of the composite material.
[0049] Figure 2 This is the X-ray diffraction (XRD) analysis of the micrometer-scale solid columnar Co / ZnO@PPy in the above-mentioned Example 1. In the figure, the diffraction peaks at 2θ=44.22°, 51.52°, and 75.85° correspond to the (111), (200), and (220) crystal planes of simple cubic Co (JCPDS No.15-0806); the diffraction peaks at 2θ=31.77°, 34.42°, 36.25°, 47.54°, 56.61°, and 62.86° correspond to the (100), (002), (101), (102), (110), and (103) crystal planes of hexagonal ZnO (JCPDS No.36-1451). The XRD spectrum analysis proves the composition information of the material, and there is no obvious impurity and mixed phase.
[0050] Figure 3 The real part (μ'), imaginary part (μ") and real part (ε') and imaginary part (ε") of the complex magnetic permeability of the micrometer-scale solid columnar Co / ZnO@PPy in the above embodiment 1 are shown in Figure 1. The real part (μ') and imaginary part (μ") of the complex magnetic permeability are used to reveal the mechanism of its excellent microwave absorption performance (μ r =μ′–jμ″). The real part of the complex dielectric constant (ε′) and the imaginary part of the dielectric constant (ε″) are used to reveal the mechanism of its excellent microwave absorption performance (ε r =ε′–jε″). As can be seen from the figure, the wave absorbing performance of the composite material mainly comes from the conductivity loss and polarization loss capacity of the dielectric loss. Compared with Examples 2 to 5, due to the increase in surface agglomeration, the electron transmission process is hindered, which reduces the conductivity loss capacity of the material, thereby affecting its loss capacity for electromagnetic waves.
[0051] Figure 4The reflection loss values of the micrometer-scale solid columnar Co / ZnO and Co / ZnO@PPy in the above Examples 1-5 in the frequency range of 2.0-18.0 GHz at a thickness of 1.7 mm. As shown in the figure, when the sample thickness of the micrometer-scale solid columnar Co / ZnO@PPy composite material is 1.7 mm, the maximum reflection loss value reaches -57.4 dB, and the effective absorption bandwidth is 5.4 GHz. Example 2- When the sample thickness of micrometer-scale solid columnar Co / ZnO@PPy is 1.7mm, the maximum reflection loss value reaches -36.4dB, and the effective absorption bandwidth is 5.3GHz; Example 3- When the sample thickness of micrometer-scale solid columnar Co / ZnO@PPy is 1.7mm, the maximum reflection loss value reaches -20.9dB, and the effective absorption bandwidth is 4.9GHz; Example 4- When the sample thickness of micrometer-scale solid columnar Co / ZnO@PPy is 1.7mm, the maximum reflection loss value reaches -27.1dB, and the effective absorption bandwidth is 5.3GHz. Example 5- When the sample thickness of micrometer-scale solid columnar Co / ZnO@PPy is 1.7mm, the maximum reflection loss value reaches -29.1dB, and the effective absorption bandwidth is 4.2GHz. At the same thickness, the microwave absorption performance of Example 1-micrometer-scale solid columnar Co / ZnO@PPy is the strongest, indicating that the in-situ gas phase polymerization reaction time is an important condition for regulating electromagnetic parameters and thus affecting the microwave absorption performance. The micrometer-scale solid columnar Co / ZnO@PPy composite material simultaneously meets the practical application requirements of strong absorption, broadband response and thin thickness, and is a potential high-efficiency microwave absorbing material.
[0052] Comparative Example 1:
[0053] Compared with Example 1, most of the steps are the same, except that the Co / ZnO powder and the pyrrole monomer are directly mixed in a sealed open bottle and allowed to stand at room temperature without in-situ gas phase polymerization.
[0054] Figure 5 The scanning electron microscope and transmission electron microscope images of the product obtained in the above Example 6 show that, without in-situ gas phase reaction, the powder and the pyrrole monomer are simply mixed at room temperature and no reaction occurs between the two.
[0055] Embodiment 6:
[0056] Compared with Example 1, most of them are the same, except that in this embodiment:
[0057] The molar ratio of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea added is 2:1:9:9. 2+ The concentration is 0.04 mol / L, Zn 2+ The concentration is 0.02mol / L.
[0058] Embodiment 7:
[0059] Compared with Example 1, most of them are the same, except that in this embodiment:
[0060] The molar ratio of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea added is 5:1:9:9. 2+ The concentration is 0.11mol / L, Zn 2+ The concentration is 0.02mol / L.
[0061] Embodiment 8:
[0062] Compared with Example 1, most of them are the same, except that in this embodiment:
[0063] The molar ratio of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea is 4:3:9:9. 2+ The concentration is 0.08 mol / L, Zn 2+ The concentration is 0.07mol / L.
[0064] Embodiment 9:
[0065] Compared with Example 1, most of them are the same, except that in this embodiment:
[0066] The molar ratio of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea is 4:2:9:9. 2+ The concentration is 0.08 mol / L, Zn 2+ The concentration is 0.04mol / L.
[0067] Embodiment 10:
[0068] Compared with Example 1, most of them are the same, except that in this embodiment:
[0069] The molar ratio of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea added is 4:1:6:9. 2+ The concentration is 0.08 mol / L, Zn 2+ The concentration is 0.02mol / L.
[0070] Embodiment 11:
[0071] Compared with Example 1, most of them are the same, except that in this embodiment:
[0072] The molar ratio of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea is 4:1:10:14. 2+ The concentration is 0.08 mol / L, Zn 2+ The concentration is 0.02mol / L.
[0073] Embodiment 12:
[0074] Compared with Example 1, most of them are the same, except that in this example, the temperature of the hydrothermal reaction is adjusted to 80°C and the time is 8h.
[0075] Embodiment 13:
[0076] Compared with Example 1, most of them are the same, except that in this example, the temperature of the hydrothermal reaction is adjusted to 160° C. and the time is 4 h.
[0077] Embodiment 14:
[0078] Compared with Example 1, most of them are the same, except that in this example, the temperature of high-temperature reduction is adjusted to calcination at 500°C for 3h.
[0079] Embodiment 15:
[0080] Compared with Example 1, most of the above are the same, except that in this example, the temperature of high temperature reduction is adjusted to calcination at 650°C for 1 hour.
[0081] Embodiment 16:
[0082] Compared with Example 1, most of the above are the same, except that in this example, the volume fraction of hydrogen in the hydrogen-argon atmosphere is 4%.
[0083] Embodiment 17:
[0084] Compared with Example 1, most of the above are the same, except that in this example, the volume fraction of hydrogen in the hydrogen-argon atmosphere is 6%.
[0085] Embodiment 18:
[0086] Compared with Example 1, most of the above are the same, except that in this example, the FeCl 3 The concentration of the ethanol solution is 3mmol / L.
[0087] Embodiment 19:
[0088] Compared with Example 1, most of the above are the same, except that in this example, the FeCl 3 The concentration of the ethanol solution is 7 mmol / L.
[0089] Embodiment 20:
[0090] Compared with Example 1, most of the contents are the same, except that in this example, the concentration of the Co / ZnO powder used is 0.1 g / mL, and the amount of the pyrrole monomer used is 1 mL.
[0091] Embodiment 21:
[0092] Compared with Example 1, most of the contents are the same, except that in this example, the concentration of the Co / ZnO powder used is 0.2 g / mL, and the amount of the pyrrole monomer used is 3 mL.
[0093] Embodiment 22:
[0094] Compared with Example 1, most of the above are the same, except that in this example, the temperature of the in-situ gas phase polymerization reaction is 50°C.
[0095] Embodiment 23:
[0096] Compared with Example 1, most of the conditions are the same, except that in this example, the temperature of the in-situ gas phase polymerization reaction is 65°C.
[0097] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a Co / ZnO@PPy composite material, characterized in that: The following steps are involved: (1) adding cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea into deionized water, stirring to dissolve, and obtaining a clear and transparent mixed solution; (2) transferring the mixed solution into a reactor for hydrothermal reaction, washing and drying the obtained reaction product to obtain a precursor powder; (3) The precursor powder is placed in a hydrogen and argon atmosphere for high-temperature reduction, and then cooled to room temperature to obtain the intermediate product Co / ZnO; (4) The intermediate product Co / ZnO is uniformly dispersed in an FeCl3 ethanol solution, the solvent is evaporated, the obtained powder is ground, and the powder is placed in the same closed container with the pyrrole monomer without direct contact with each other, and heated to perform an in-situ gas phase polymerization reaction. The obtained reaction product is washed and freeze-dried to obtain the target product Co / ZnO@PPy; In step (1), the molar ratio of cobalt nitrate hexahydrate, zinc nitrate hexahydrate, ammonium fluoride and urea is (2-5): (1-3): (6-10): (8-14); In step (1), the amount of deionized water added satisfies: 2+ The concentration is 0.04~0.12 mol / L, Zn 2+ The concentration is 0.01~0.07 mol / L.
2. The method for preparing a Co / ZnO@PPy composite material according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal reaction is 80-160° C. and the time is 4-8 hours.
3. The method for preparing a Co / ZnO@PPy composite material according to claim 1, characterized in that: In step (3), the volume fraction of hydrogen in the hydrogen-argon atmosphere used is 4-6%.
4. The method for preparing a Co / ZnO@PPy composite material according to claim 1, characterized in that: In step (3), the high temperature reduction process is specifically: calcining at 500-650°C for 1-3h.
5. The method for preparing a Co / ZnO@PPy composite material according to claim 1, characterized in that: In step (4), the concentration of the FeCl3 ethanol solution is 3-7 mmol / L, and the concentration of Co / ZnO in the FeCl3 ethanol solution is 0.1-0.2 g / mL.
6. The method for preparing a Co / ZnO@PPy composite material according to claim 1, characterized in that: In step (4), the temperature of the in-situ gas phase polymerization reaction is 50-65° C., and the reaction time is 2-24 h.
7. A Co / ZnO@PPy composite material, prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The composite material is a micrometer-scale solid column with a circular cross-section size of 2 to 3 μm and a honeycomb structure on the surface.
8. The use of a Co / ZnO@PPy composite material as claimed in claim 7, characterized in that: The composite material is used as a microwave absorbing material.
Citation Information
Patent Citations
Preparation method for sandwich-structured cobalt-nickel alloy particle / reduced graphene composite material
CN109054741A
Morphology-controllable CoSe2 / Ti composite material and preparation method thereof
CN111349915A